KOMIKA STAND UP COMEDY DALAM PERSPEKTIF INDUSTRI BUDAYA (STUDI KASUS PANDJI PRAGIWAKSONO) - Triana, Nunik (Faculty of Communications Science, Dr. Soetomo University, 2021)
This paper reviews the position of stand up comic from the perspective of the culture industry by Theodor Adorno. In Adorno's view, the culture industry is always commercially oriented and therefore works or products that carry the character of artistic or cultural values will not be born because these products exist only to respond to market tastes formed by the capitalists. In this case, the artists will not be able to survive if they stick to idealism. With a qualitative approach and critical paradigm, the author takes stand up comic Pandji Pragiwaksono as a case study. The results of the analysis show that Pandji's figure as comic defeats Adorno's criticism. Pandji proves that art in culture industry is able to be an enlightening product, which do not just fulfill market tastes and follow homogeneous standards that set by capitalists. Especially on Pandji's works, it also has messages that can encourage people to think critically. Pandji also proved that he can make a good living by working as comic.